The cumulative impact of parental migration on schooling of left-behind children in rural China. (August 2021) - Dong, Yongqing; Wang, Weidong; Li, Shaoping; Zhang, Linxiu
Abstract: It is widely known that parental migration for off-farm employment plays an important role in the livelihoods of families in rural areas of developing countries. Undoubtedly, it has made contributions to poverty reduction, income increases, and the strengthening of the consumption capacity of rural families. However, research on whether it has a long-term effect on the schooling of laborers' children is still scarce despite the short-run effect of parental migration on children's academic performance receiving considerable attention in recent empirical research. This paper investigates the impact of parental migration for off-farm employment on the schooling years of left-behind children in rural China. We draw on a unique dataset collected by the authors themselves through the nationally representative China Rural Development Survey. By using ordinary least squares and the family fixed effects model, our results show that parental migration increases the educational investment in children, while it has no effect on the schooling years of left-behind children. It implies previous studies using the contemporaneous measure for parental migration might overestimate the adverse effect of exposure to parental migration on children's schooling years. This study makes two contributions to the literature – one, it is the first study in the china context on the cumulative impact of parental migration on schooling years of left-behind children and second, it applies the family fixed effects model to alleviate the endogeneity problems. Highlights: We investigate the cumulative impact of parental migration on the schooling of left-behind children in rural China. We draw on a unique dataset collected by the authors themselves through the China Rural Development Survey. Our results show that the accumulated years of parental migration has no effect on schooling of the left-behind children. Parental migration would tend to increase the educational investment in their children.